DIRECTIONS FOR INCREASING THE EFFICIENCY OF INDUSTRIAL PROCESSING OF AGRICULTURAL PRODUCTS - Saidova, Gulnoza Tulkunovna (THE INNOVATION ECONOMY, 2025)
industrial processing of agricultural products in the article scientifically based proposals and recommendations on the directions of increasing the efficiency of the processes are given. Also, the current state studied and analyzed of processing agricultural products.